The Effect of Wordwall Media on Early Childhood Language Skills at TKIT Al-Kaukaba - Mulyawati, Susi; Budiarti, Erna (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The purpose of the research is to determine the influence of wordwall media on early childhood language skills in TKIT Al-Kaukaba. This study uses a quantitative approach using a quasi-experimental method using a Nonequivalent control group design. In this study, the population taken was all children of group B TKIT Al-Kaukaba totaling 30 students. The sampling technique in this study is total sampling, while the samples taken are TKIT Al-Kaukaba students with B1 group students of 15 children as the experimental group and B2 group of 15 children as the control class. The instrument in this study is an observation sheet of children's language skills. The data analysis technique using the mean difference test for two paired samples (unpaired sample t-test) was carried out to assess the data using SPSS software. The results of the study showed that there was a difference in the level of children's language proficiency between children who obtained the wordwall method compared to students who did not obtain the wordwall method